Credit Risk Management and Financial Performance: A Case of Union Bank Nigeria Limited - Chidinma Nwachukwu C. (International Studies Journal)
The purpose of the study was to determine the link between credit risk management and Union Bank financial performance. The research took a case study approach and used both quantitative and qualitative methods. According to the study, the Bank has attempted to diversify geographically not just inside the country, despite the fact that the majority of loans are issued to different regions within the country, but also into neighboring countries such as Tanzania. The bank has approximately 35 branches around the country, including 21 in the center region and 14 in the north. Strong credit appraisal lays the groundwork for efficient credit risk management and gives businesses a competitive advantage in the marketplace. As a result, credit appraisal determines a bank's survival and profitability. At a 95% confidence interval, the adjusted R Square value was 0.978, indicating that the bank's performance varied by 97.8% due to changes in client appraisal, credit risk control, and risk diversification. The report suggests that the Bank's management evaluate their risk management procedures on a regular basis to check if they are still effective in the face of a constantly changing operating environment, such as new regulatory frameworks. For ease of understanding, the items should be customized to the local language. The study is unique in that it suggests a link between credit risk management and bank performance. These findings are useful for scholarly comprehension as well as policy formation by the bank's decision makers.